KEMELUT POLITIK THAILAND TAHUN 2023: ANTIKLIMAKS JALAN PERUBAHAN MENUJU DEMOKRASI - Walangara Nau, Novriest Umbu (Universitas Jenderal Ahmad Yani, 2025)
Move Forward, a progressive party secure a historic win in the 2023 Thailand general election and nominated Pita Limjaroenrat as the new Prime Minister. However, Move Forward was thwarted in parliament and betrayed by its coalition partner Pheu Thai which shifted to support the royalist party. The anticlimax of Move Forward's victory poses a major challenge to Thailand's efforts towards a more democratic direction. This paper examines the dynamics of Thai politics and its prospects for democracy after the 2023 election by utilizing the idea of ​​Constructivism and employing a literature study method. This paper argues that Move Forward's victory is a strong signal of the waning public support for pro-military and royalist parties. Move Forward's ability to attract the support of Pheu Thai loyalists and to win the upcoming election with sufficient margin of victory are going to be pivotal.